Respons Pertumbuhan dan Hasil Jagung Manis serta Sifat Kimia Tanah Alfisol terhadap Aplikasi Pupuk Organik dan Anorganik - Bardhian Cahyo Aji Gumilang; Jauhari Syamsiyah; Muhammad Ziaul Haq Faiz; Aditya Fajar Pamungkas; Amanda Elena; Raihana Dzatul Akmam; Maheswari Putri Ramadhani; Zahwa Aliyatul Fatikha; Zahwa Khoirun Nisa (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
Sweet corn (Zea mays saccharata) is a horticultural commodity with high economic value and increasing market demand in Indonesia. However, national sweet corn productivity remains low compared to its genetic potential due to limited soil fertility, especially in Alfisols. To overcome this issue, this study aims to examine the effect of various fertilizers on the growth and yield of sweet corn, as well as changes in the chemical properties of Alfisols. The research method employed a completely randomized design (CRD) with a single factor and four treatments: control (without additional fertilizer), NPK 15-15-15 fertilizer, cow manure, and a combination of NPK 15-15-15 fertilizer and cow manure, each replicated three times. Plant growth and yield data (plant height, stem diameter, leaf number, ear weight, ear number, ear diameter, husked ear weight, and fresh weight) and soil chemical properties (pH, organic C, N, P, K) were analyzed using ANOVA followed by a 5% DMRT. The results showed that the combination of NPK 15-15-15 and cow manure produced the best growth and yield with an average plant height of 183.5 cm and ear length of 35 cm. These findings indicate that the combination of organic and inorganic fertilizers has the potential to improve sweet corn productivity and contribute to the soil's chemical quality in Alfisols.